Odpowiedzi

2010-02-22T18:26:40+01:00
A) x+4=6 /-4
x= 6-4
x=2
b) y-3=9 /+3
y=12
c) 3x=2+4
3x=6 / :3
x=2
d) 7= 2y-1 /+1
8=2y /:2
y=4
e) 6w-4=4w /-4w+4
2w=4 /:2
w=2
f)2t + 5 = 5t - 1 / -2t+1
6=3t /:3
t+2

14 4 14
2010-02-22T18:31:07+01:00
A)
x + 4 = 6
x=6-4
x=2

b)
y - 3 =9
y=9+3
y=12

c)
3x = 2 +4
3x=6/:3
x=2

d)
7= 2y -1
2y=7+1
2y=8/:2
y=4

e)
6w - 4 =4w
6w-4w=4
2w=4/:2
w=2

f)
2t + 5 = 5t - 1
5t-2t=5+1
3t=6/:3
t=2
48 1 48
2010-02-22T18:35:10+01:00
A)x+4=6
x=6-4
x=2
b)y-3=9
y=9+3
y=12
c)3x-2=4
3x=4+2//3
x=2
d)7=2y-1
7+1=2y //2
y=8
e)6w-4=4w
6w-4w=4
2w=4//2
w=2
f) 2t+5=5t-1
2t-5t=-1-5
-3t=-6//-3
t=2

//- to oznacza dzielenie obustronne ;D
3 5 3